A Concept Paper: How Does Spirituality Affect Individual’s Thought, Emotion, Behaviour, Mental and Physical Health? - Asa Ismia Bunga Aisyahrani; Lina Handayani; Aufatcha Ayutya Suryana (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Spirituality can be understood through several approaches. Based on the Islamic perspective, spirituality is defined as the outcomes of faith in Allah including belief in infinite power, the perfection of Allah and belief in life after death, which create meaningful and purposeful human life situations. Spirituality leads to happiness, hope, comfort, and it leads to physical and mental health. Objective: Therefore, this paper aims to discuss the effect of spirituality toward thought, emotion, behaviour, as well as mental and physical health. Method: This paper employs library research. The authors study several literatures related to the topic of the paper. Result: Spirituality helps people to be tough and cope with stress. It makes them in a good state of mental and physical health. Conclusion: Spirituality affects positively toward people behaviour, emotion, and make them in good health and well-being.